On the performance, economic, and environmental assessment of integrating a solar-based heating system with conventional heating equipment; a case study. (October 2019) - Haghghi, Maghsoud Abdollahi; Holagh, Shahriyar Ghazanfari; Pesteei, Seyed Mehdi; Chitsaz, Ata; Talati, Faramarz
Highlights: Performance, exergoeconomic, and environmental facets of a solar heating system are analyzed. Flat plate solar collectors are used as the prime movers of the system. The highest heating loads in warm and cold days are 37.52 kW and 91.05 kW, respectively. The maximum payback period of the proposed system is 3.1 years. Employing the system contributes to 84.67 kg/MWh and 84.71 kg/MWh reductions in CO2 emission rate. Abstract: In this paper, the performance, economic, and environmental aspects of integrating a flat plate solar collectors (FPSC)-based system with conventional heating equipment fueled by natural gas are evaluated for a residential building, located in Urmia city, Iran. The main component of the conventional domestic heating equipment is a hot water boiler, powered by a burner. Generally, the present analysis is divided into two parts. The first part is based on analyzing the system for 12 daylight hours in which solar radiation is available, while the second part evaluates it for 12 night hours. To provide the heating load of the building during daylight hours, the solar-based system is used, and the conventional equipment is utilized at night hours. The real heating load of the building constituted of the total load relevant to hot consumed water and the building thermal loss rate in cold months and the available solar radiation are calculated and employed in the simulations. Also, the monthly average total solar radiation, applied in the simulations, is between 7.63 MJ/m 2 /day and 25.39 MJ/m 2 /day throughout a year. The results revealed that the highest heating load for air conditioning purposes in warm and cold days are 37.52 kW and 91.05 kW, respectively. Furthermore, the highest heating load is provided using 63.3 m 2 and 443.8 m 2 of FPSCs for hot and cold air conditioning, correspondingly. Besides, the maximum payback period of coupling the FPSCs with the conventional equipment is found to be 3.1 years. Also, the employment of FPSCs contributes to reductions in CO2 emission rate with values of 84.67 kg/MWh and 84.71 kg/MWh for cold and warm days, respectively.